MODIFIKASI HIBRID SEBAGAI UPAYA MENOPANG KEMANDIRIAN ENERGI LISTRIK SKALA RUMAH TANGGA - Teguh Yuwono; Ari Prasetiyo; Irfan Ansori (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2020)
Ministry of Energy and Mineral Resources (ESDM) states that Indonesia's electricity consumption in 2017 reached 1,012 kWh per capita, up 5.9 percent from the previous year. Utilization of potential mechanical energy sources for electric water pumps as part of the need for household electrical equipment has the opportunity to be developed into a hybrid source through the mechanism of conversion of mechanical energy into electricity through direct current (DC) mini generators. Mini DC generator is a modified component unit which converts mechanical energy into DC electrical energy which is connected to the shaft where the electric motor fan pumps water. When an electric water pump is used in daily use in the household, mechanical energy that arises in the electric motor is used to produce dc electrical energy through a mini generator that is coupled to the water pump motor. DC electrical energy from the conversion of the mini generator will be supplied to the mini generator unit as a tool that functions to change the dc to dc or dc to ac voltage which is practical for the purposes of electricity backup or as an alternative source of additional household-scale energy with a hybrid source. The mini generator set unit is equipped with an Auto Transfer Unit (ATS) unit and a charger cut-off battery charger unit. The working principle of ATS uses relay components, which is when the main power source experiences blackouts or interference, then the ATS unit will automatically divert the main electrical energy supply to an additional electrical energy source or hybrid source. This research produced a hybrid system modification method to sustain electrical energy of 17.2 kWh and a cost savings of Rp. 10,398 every month, the application was in the form of a prototype product supporting a mini generator capacity of 500 watts pure sine wave (PSW) with an energy source from modification of a hybrid mini generator.